Comunicación vertical y clima laboral del personal operativo de la empresa de transportes Nuevo California S.A., 2022 - Garcia Paredes, Sheila Brilly (2023)
The present investigation was carried out with the objective of analyzing the influence of vertical communication in the work environment of the operating personnel of the Transport Company Nuevo California S.A. For this, a sample of 138 drivers was taken, who are male, whose ages range from 30 to 60 years. The methods used in this research were inductive-deductive, analytical-synthetic and statistical, in the same way research techniques such as survey and interview were used that allowed obtaining quantitative and qualitative information. The data collection instruments that managed to capture the necessary information were the questionnaire, interview guide and interview record, which have allowed us to understand the dynamics of the variables and develop the present investigation. The results obtained show that the practice of vertical communication in the company does not allow constant feedback to be given, affecting the dimensions of the work environment such as interpersonal relationships, which is deficient because there is no adequate integration and interaction, as well as demotivation. and deficient work performance in the operational personnel because they do not feel that their work is valued, so 73.19% indicate that they do not usually receive congratulations or words of praise from their boss for the work they do, likewise 72.46% do not know what the objectives and goals of the company are, denoting that there is no commitment and identification with the company.